Bay-region functionalisation of Ar-BIAN ligands and their use within highly absorptive cationic iridium(III) dyes - Kamrul Hasan (2018)
We report the synthesis, UV-vis absorption, electrochemical characterisation, and DFT studies of five panchromatic, heteroleptic iridium complexes (four of which are new) supported by Ar-BIAN ligands. In particular, the synthesis of an ester-functionalised Ar-BIAN ligand was carried out by a mechanochemical milling approach, which was advantageous over conventional metal templating solution methods in terms of reaction time and product purity. The introduction of ester and carboxylate functionalities at the bay region of the acenaphthene motif increases each ligand’s π-accepting capacity and imparts grafting capabilities to the iridium complexes. These complexes have absorption profiles that surpass the renowned N3 dye [Ru(dcbpy)2(NCS)2] (dcbpy = 4,4′-dicarboxy-2,2′-bipyridine), making them of interest for solar-energy-harvesting applications.